ANALISIS TAX AVOIDANCE PADA EMITEN KONSTRUKSI: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Santi, Santi; Maisyarah, Renny; Br Purba, Rahima (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
Tax avoidance is a legal tax management strategy carried out in accordance with taxation regulations, yet it often raises a dilemma because, while permitted, such practices are generally discouraged by tax authorities due to their impact on state revenue. The phenomenon of tax avoidance in Indonesia continues to rise, particularly in the construction industry sector, which is characterized by long-term projects and complex financing structures. These unique characteristics make the sector especially vulnerable to aggressive tax planning strategies. This study aims to analyze the influence of firm size, profitability, leverage, and institutional ownership on tax avoidance practices among construction companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Utilizing a quantitative approach, this research is based on secondary data drawn from annual reports and audited financial statements. The sample consists of 17 companies selected through purposive sampling, and the data were analyzed using multiple linear regression models with SPSS version 24. The empirical results show that firm size has a positive and significant effect on tax avoidance, suggesting that larger firms possess more resources and capacity to engage in sophisticated tax planning. While, profitability, leverage, and institutional ownership did not show significant effects, implying that these factors are not decisive in determining the tax avoidance behavior of companies in this sector. These findings are important both theoretically and practically. Based on Agency Theory where managers of larger firms may exploit available mechanisms to reduce tax burdens—while also challenging the expectations of signaling theory, particularly regarding the role of profitability. From a practical perspective, the study highlights the need for tax authorities to focus enforcement and monitoring efforts on large-scale firms, as they demonstrate a higher propensity for engaging in tax avoidance. Additionally, the findings call for a reassessment of existing regulatory frameworks and supervisory mechanisms in order to improve compliance without discouraging legitimate tax planning activities.